An Evaluation of Website Usability for a Cover Crops Resource in the Southern Region - Emily Cabrera; Jessica Holt (Journal of Applied Communications, 2020)
With shifting demographics of agricultural professionals, online educational resources present opportunities for Extension and other natural resources faculty and personnel to use various tools for supporting agricultural producers in the 21st century using more modern technology. Traditionally, Agriculture and Natural Resource (ANR) Extension programming has used a variety of hands-on methods for teaching new, more sustainable farming practices, such as on-farm field days, workshops, farm visits, and demonstrations. While these traditional teaching methods are preferred among farmers, online support tools play a critical role in the overall decision-making process for farmers who are considering making changes to their current farming practices. Online educational resources, with mobile-friendly versions, can be used to assist Extension and Natural Resource Conservation Service (NRCS) agents meet the needs of their clients using more modern forms of technology, whether from the office or on-farm. This study employed two focus group discussions with Extension and NRCS agents and university faculty members to evaluate the usability of a cover crop website that could be used as a support tool for a variety of agricultural professionals. Four themes emerged from this study with reference to a simple, clean appearance; efficient browsing; process-thinking design; and mobile- friendly. This research will be used to inform the continued development of website tools to benefit farmers, producers, agents, and other stakeholders.
Keywords: website usability; online resources; new media